Six new Leguminosae-Papilionoideae of Mexico - Rzedowski, Jerzy; Calderón de Rzedowski, Graciela (Instituto de Ecología, A.C., 2015)
The following taxa are described as new and illustrated: Astragalus guanajuatensis, related to A. purpusii; Dalea emmae, also from Guanajuato and belonging to the section Cylipogon; D. estoraxana, from Querétaro, apparently related to D. melantha var. berlandieri; D. lutea var. longispica, from the Sierra Madre Oriental of Nuevo León, Guanajuato and Querétaro, different from the three already known varieties of the species; D. rosarum, only known from a short segment of the Sierra Madre Oriental in Querétaro and possibly related to D. botterii; as well as D. rupertiana, from northeastern Guanajuato, which belongs to the section Parosela, but does not fit to any of its series defined by Barneby.